Development of CAPINA Blenderized Formula Based on Banana, Mung Bean Extract, Chicken Breast, and Dragon Fruit as a Low-Sodium and Low-Fat Liquid Diet in Bhayangkara Hospital, Kediri - Fadillah Diana Lukman; Ariqah Hidayatun Nisa’; Friska Juniarda; Nelli Nafidatul Isfanah; Novita Dwi Arianti; Pinky Apriliawan; Suci Rahayu; Ana Nur Filiya; Nanik Hamidah; Rr Lieliesnaini Octaviariani Sutoyo; Nuzul Dwi Utami (Ficco Public Health Journal, 2026)
Background: Meeting the nutritional requirements of hospitalized patients receiving low-sodium (LS) and low-fat (LF) liquid diets remains a significant clinical challenge, particularly due to the frequent use of tajin as the main liquid diet, which provides inadequate energy and protein. Insufficient nutritional intake may increase the risk of hospital malnutrition and adversely affect clinical recovery. This study aimed to develop a CAPINA blenderized formula based on banana, mung bean extract, chicken breast, and dragon fruit as a nutritionally improved liquid diet alternative, and to evaluate its nutrient composition, acceptability, and cost-effectiveness. Methods: A true experimental study was conducted using a posttest-only control design with a Completely Randomized Design (CRD). Two formulations were developed: F0 (without dragon fruit) and F1 (with the addition of 10 Gram of dragon fruit). Nutrient composition was assessed using quantitative descriptive analysis, while acceptability was evaluated based on color, aroma, texture, and taste by 10 panelists using a hedonic scale. Cost analysis was performed to assess the economic feasibility of each formulation. Results: The results showed that the energy content of F0 and F1 was 285.4 kcal and 281.7 kcal, respectively, with comparable protein contents of 15.38 Gram and 15.45 Gram. Both formulations met the criteria for LS and LF diets due to their low fat content. Acceptability testing demonstrated higher overall acceptance for F1, particularly in color (100%) and taste (93%). High acceptance was also observed for aroma and texture in both formulations. Cost analysis indicated that F1 was more cost-effective than F0. Conclusion: In conclusion, the CAPINA blenderized formula, particularly formulation F1, represents a promising alternative to tajin for hospitalized patients requiring LS and LF liquid diets, as it provides improved nutritional adequacy, high acceptability, and favorable cost-effectiveness.